TINGKAT KESIAPAN KAWASAN INDUSTRI TERAS-MOJOSONGO KABUPATEN BOYOLALI SEBAGAI KAWASAN GREEN INDUSTRY - Sri Untari, Galuh; Hardiana, Ana; Putri, Rufia Andisetyana (Region : Jurnal Pembangunan Wilayah dan Perencanaan Partisipatif, 2017)
The industrial sector is one of the leading sector in Boyolali. There are several industrial area in Boyolali, one of them is Teras-Mojosongo Industrial Area. Teras-Mojosongo Industrial Area has been designated as one of a national-scale industrial area by the Ministry of Industry which is planned to be completed at 2016. The development of industrial area can not be separated from the impact to it’s  environment. Green industry is  a concept of industrial area development to face environmental challenge and global economic crisis. Therefore the concept of green industry should be applied in the development of Teras-Mojosongo Industrial Area. This concern has to increase industrial economic growth and preserve environment. The question on this research is to know the readiness of  Teras-Mojosongo Indutsrial Area as green industry area seen from characteristic (1) green plan, (2) green process, (3) green management, and (4) green policy. This research is a quantitative research using scoring analysis technique. Based on the analysis, the result shown that the level of readiness of Teras-Mojosongo industrial area as green industry area is close to ready. Therefore some of green industry characteristics that need to beimproved, such as green management characteristic and green policy characteristic. In order to increase the whole readiness of the green industrial area ind Teras-Mojosongo Boyolali.